Study of heterogeneity of sino-nasal lesions in urban population of north Kolkata and its fringes- a 5-year retrospective analysis: experience of a tertiary care centre - Bhattacharyya, Debosmita; Das, Tushar Kanti; Mukherjee, Sanghamitra; Mahata, Manisha (International Journal of Research in Medical Sciences, 2017)
Background: Lesions of the nasal cavity and paranasal sinuses form a single functional unit as both of these are affected by common pathological processes. Accurate diagnosis and early treatment can significantly reduce the morbidities associated with these lesions. This study aims at portraying the morphological diversions of sinonasal lesions that is commonly encountered in populations of north Kolkata and its fringes. The multitude of histopathological variations of the sinonasal masses intrigues us histopathologists not only from academic point of view but also guides clinicians regarding treatment and prognosis. Methods: A retrospective study conducted in the Department of Pathology from May 2012 to April 2017. Results: Total 429 cases were assessed during this period out of which maximum cases were found in the age group of 31- 40years. Most cases were diagnosed with nasal polyps. The rare histopathological types were ameloblastoma, paraganglioma, Schwanoma, neurofibroma, inflammatory myofibroblastic tumor, sinonasal hemangiopericytoma, adenoid cystic carcinoma, low grade mucoepidermoid tumor, malignant peripheral nerve sheath tumor. Conclusions: Both neoplastic and non-neoplastic sino nasal lesions may present with indistinguishable features, leading to a delay in proper diagnosis and treatment. So, any tissue after surgical removal should be send for histopathological diagnosis without unnecessary delay to prevent further complications.